Kajian Dampak Restorasi Mangrove Terhadap Sosial Ekonomi Masyarakat Desa Teluk Pambang Kecamatan Bantan Kabupaten Bengkalis Provinsi Riau - Berutu, Nurmala; Yenny, Novida; Sidauruk, Tumiar; Permana, Sendi; Harefa, Meilinda Suryani; Tuhono, Eling; Junaidi, Junaidi (Ecoplan, 2024)
Restoring degraded mangrove ecosystems is crucial in order to enhance the sustainability of coastal ecosystem environments, conserve biodiversity, and provide social, economic, and environmental benefits to communities. The objective of this research is to examine how mangrove restoration activities can contribute positively to the socio-economic livelihoods of the community in Teluk Pambang, Bengkalis Regency. The study was conducted using a descriptive qualitative approach and implemented in early November 2023. Data was collected in multiple ways, such as observation and documentation. The results showed that mangrove restoration activities provided several impacts. First, it was good for increasing community knowledge and understanding of the function and role of mangroves in coastal conservation efforts. After that, it enhanced community empowerment through the formation of agricultural groups such as Belukap and Langgadai, with 62.50% of group members actively participating in restoration activities from land clearing to planting stages. Finally, mangrove restoration activities conducted in Teluk Pambang village contributed positively to increasing the income of community members. Certainly, restoration activities have been perceived as highly beneficial in helping meet the daily needs of the families of agricultural group members. Therefore, it is hoped that the mangrove restoration efforts in Teluk Pambang village can be done sustainably.